Impactos socioambientais decorrentes do uso de agrotóxicos oriundos de contrabando - Vezzosi, Silvana Wallau (2020)
The present study aims to identify the extention of the socio-environmental damage caused by the use of illicit pesticides from contraband, in the country and, essentially, in the State of Rio Grande do Sul. Thus, the research was divided into three chapters: the first intended to study the socio-environmental impacts and the political-economic barriers implemented by the pesticide economy, with an emphasis on Bill 6.299 / 02, entitled “poison law”; the second proposes an analysis of the observed and emerging damages related to cases potentially linked to the use of ilegal pesticides, through inferences from inspection and research activities and to associate them with the merely repressive action of the State, in a risky society; the third makes an analysis of the legal issues related to the contraband of pesticides, the issue related to border control and the necessary and possible measures to combat the practice. The methodology and the action strategy that made the present research feasible follow the trinomial basic theory / approach, procedure and technique. As a basic theory, a systemic-complex perspective was chosen in view of the interdependent areas of knowledge (political, economic, biological, legal and environmental), considering that the isolated approach has no potential to elucidate the complexity present in socioenvironmental issues. . The procedure used consists of bibliographic and documentary research (in physical and digital media), study applied to cases and comparative analysis. We conclude that the actual and potential damage caused by the contraband of pesticides is far from being measured in its real magnitude because of a lack of reliable information or research that can point them out in concrete terms. In addition, the motivators of illicit practices related to the illegal introduction of pesticides in the country are of various types, including the lack of pattern of legislation in the countries of the Southern Common Market, the lack of control and peculiarities of national borders and the lack of effective prevention and coping public policies strategies. Thus, it is urgent to adopt attitudes that seek the solution - or at least restraint - of the current conjuncture, which must originate from institutionalized policies that encompass several aspects, including the alteration / creation of international agreements and securitization of borders, among others.